PENGARUH PROBLEM BASED LEARNING TERHADAP LITERASI SAINS PADA PEMBELAJARAN FISIKA: META-ANALISIS - Nur Fadilah, Afifah; Suwarna, Iwan Permana; Hertanti, Erina (UIN Sunan Gunung Djati Bandung, 2025)
This meta-analysis aims to analyze the impact of Problem-Based Learning (PBL) on students’ science literacy in physics education. The study uses a descriptive quantitative method with a meta-analysis approach on 16 national journal articles that meet inclusion and exclusion criteria. Results indicate a significant average effect size of 1.72 (large category), with senior high school (effect size 1.95) having the most critical impact. In contrast, junior high and elementary schools have effect sizes of 0.77 and 0.48, respectively. Problem-based learning significantly impacts the Solar System, Heat & Temperature, and Global Warming. Furthermore, the implementation factor with the most significant and consistent impact is PBL combined with learning media, especially edugames and interactive simulations, with an average effect size of 1.76 (large category). These results suggest that PBL in physics education can significantly improve students’ science literacy, especially in higher education levels and with appropriate learning media.